1988
DOI: 10.1016/0266-7681(88)90105-2
|View full text |Cite
|
Sign up to set email alerts
|

Synovial hand infection from mycobacterium terrae

Abstract: A case of extensive synovial infection in the hand due to Mycobacterium terrae is described. The infection is resistant to drug therapy but appears to remain localised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…2,6 Orthopedic infection caused by the M terrae complex (M terrae, Mycobacterium nonchromogenicum, and Mycobacterium triviale) and related species has been infrequently described. [7][8][9][10][11][12][13][14][15][16][17][18][19] Most cases of orthopedic infection caused by the M terrae complex involve the tenosynovium of the hand and wrist. 6,8,[10][11][12][13][14]16,17 To the authors' knowledge, only 3 cases of M terrae infection in large joints have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…2,6 Orthopedic infection caused by the M terrae complex (M terrae, Mycobacterium nonchromogenicum, and Mycobacterium triviale) and related species has been infrequently described. [7][8][9][10][11][12][13][14][15][16][17][18][19] Most cases of orthopedic infection caused by the M terrae complex involve the tenosynovium of the hand and wrist. 6,8,[10][11][12][13][14]16,17 To the authors' knowledge, only 3 cases of M terrae infection in large joints have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In 1967, the Centers for Disease Control in the United States reported 5 clinically significant cases of M terrae infection. Over 50 cases of M terrae infection have been reported, involving bone and other synovial structures, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] lungs, [19][20][21][22] skin, 19,23 gut, 24 urinary tract, lymph nodes or disseminated disease. 19,23,25 The most common site is the tenosynovium of the hand and wrist.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,14 However, M. terrae complex, as well as other mycobacterial pathogens, is frequently unidentified even with Ziehl-Neelsen preparation, and only indirect findings of mycobacterial infection (granulomatous inflammation with or without caseation, giant cells, lymphocytic infiltration, and focal fibrinoid necrosis) are found, which may serve as the initial suspicion of closed-space atypical mycobacterial infection. 10,12,14 However, M. terrae complex, as well as other mycobacterial pathogens, is frequently unidentified even with Ziehl-Neelsen preparation, and only indirect findings of mycobacterial infection (granulomatous inflammation with or without caseation, giant cells, lymphocytic infiltration, and focal fibrinoid necrosis) are found, which may serve as the initial suspicion of closed-space atypical mycobacterial infection.…”
Section: Histological and Microbiological Findingsmentioning
confidence: 99%
“…2,6 In addition, some cases of M. terrae joint infection have resolved with surgery alone 1,4,14,16 or with surgery and antituberculosis chemotherapy. Although antimycobacterial agents rifampin and isoniazid have been used to treat M. terrae complex infections, they have not been established as a standard of care or as empiric therapy because of the paucity of data and variable success.…”
Section: In Vitro Antibiotic Susceptibility and Treatment Of M Terramentioning
confidence: 99%